Gender variation in operative findings and outcome in patients undergoing laparoscopic cholecystectomy at Birat Medical College Teaching Hospital - Charan Shrestha, Bhupendra; Sharma, Shivraj; Narayan Shah, Dhurba; Pandit, Narendra; Adhikari, Milan; Sharma, Ismita (Birat Journal of Health Sciences, 2024)
Introduction: Laparoscopic cholecystectomy is the gold standard treatment for symptomatic cholelithiasis. Despite advancement in surgical instrument and operating technique, conversion to open cholecystectomy is still worrisome concern to surgeons. There are various preoperative factors impacting on conversion. Male gender as an independent risk factor for conversion is still debatable. Ojectives: This study aims to study the role of male gender, its impact on operative findings and conversion. Methodology: A total number of 131 patients diagnosed as symptomatic cholelithiasis and who fulfilled the inclusion criteria underwent laparoscopic cholecystectomy. Data related to patients demographics like age sex, intraoperative complications like bleeding, bile leak, duration of surgery, conversion if any was noted. Reason for conversion was also noted. Postoperative complications like pain, surgical site infection and duration of hospital stay was noted. Results: In this study, A total of 130 patients participated in this study of which 64 (51.70%) were male (M) and 66 (44.89%) were female (F). Mean age of presentation was 48.25 years, youngest being 23 years and elder being 78 years of age. Mean operating time was 40.66 minutes. Bile leak was seen in 2 patients in male (M) group while no such event was observed in the female group (p value 0.240). There was no organ injury observed in either group. 1 patient in the female (F) group had postoperative pancreatitis (p value 1.00). Postoperative obstructive jaundice was noted in 2 patients in female group (F), p value 0.496. It was observed that 7 male patients had conversion to open during the procedure while only 3 cases were converted in the female gender group, p value of 0.203. Bile duct injury was seen in 1 patient in male (M) gender group, p value 0.492. However, this injury was not seen in the conversion group. All cases undergoing conversion had mean operating time of 75.3 minutes and this was more in male (M) group. Conclusion: Laparoscopic cholecystectomy is difficult in male (M) gender group compared to females and operating time is also longer, however male gender is not an independent risk factor for conversion.